ANALISIS PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN DENGAN MENGGUNAKAN,BENEISH RATIO INDEX (Studi,Pada,Perusahaan Sektor,Manufaktur yang Terdaftar di Bursa,Efek,Indonesia Periode 2016-2017) - Islami Putri Apriani; Nila Firdausi Nuzula (Fakultas Ilmu Administrasi Universitas Brawijaya, 2019)
Companies always want to show that they are in good financial conditions. Companies sometimes commit financial statements fraud to make its financial conditions look good. This study aims to find out how many manufacturing sector companies listed on Indonesia Stock Exchange (IDX) in 2016-2017 commit fraudulent financial statements and analyzed the loopholes used in conducting fraud. This research is a descriptive study with a quantitative approach. The indicators that used were eight variables of Beneish ratio index and M-score based on Beneish's 1999 findings in his journal